Indigeneity of Neoliberalism in Mongolia’s Nation Building - Bumochir, Dulam (Vilnius University Open Series, 2025)
In brief, this paper shows the different consequences being contested in the process of nation building in Mongolia. Among the different consequences, I focus on what is called the liberal economy and market, which represent neoliberalism in Mongolia. I contextualize this through an analysis of the reconstruction of history and the continuity of the Mongolian legal system. These are the main contesting features that have consequences in Mongolian nation-building. In the contest, the historical reconstruction and the legal continuity are widely acknowledged and promoted by the public, and they remain the main force to justify the bills and political decisions to limit and tame some principles of neoliberalism. I argue that restricting and taming neoliberalism is a process to indigenize forms of neoliberalism employed in Mongolia’s nation-building project.